Hubungan Antara Faktor Sosiodemografi, Sosioekonomi Dan Sosiobudaya Dengan Pencarian Pengobatan Malaria Di Puskesmas Kaligesing Kabupaten Purworejo - I Made Satya Purnama (Universitas Pekalongan, 2020)
Malaria cases are widely found in Indonesia with 30.000 of death every year. Purworejo is one of endemic area of malaria in Indonesia. There is increasing of malaria cses every year in Purworejo. Furthermore, people in Purworejo assume that malaria is so common disease. The research was observational-analitic research with cross sectional design. Number of sample were 70 people.Sample of research consisted of two group, which are malaria patient who got medical treatment and malaria patient who got traditional treatment. Analysis of relationship between independence and dependence variable was tested by Chi-Square test. Meanwhile analysis of most influential variable applied logistic regression. There were four variables related with malaria seeking care, gender, belief, knowledge and perception of seriousness. Variable that simultaneously affected malaria seeking care were knowledge and perception of seriousness. Meanwhile the most influential variable was perception of seriousness. Keyword : Health Seeking Behavior, Malaria